2012
DOI: 10.1177/0260106013510994
|View full text |Cite
|
Sign up to set email alerts
|

Food choice and meal consumption pattern among undergraduate students in two universities in Southwestern Nigeria

Abstract: The food choices and meal consumption patterns of undergraduate students from two Nigerian universities, Obafemi Awolowo University, Ile-Ife (OAU) and Adekunle Ajasin University, Akungba Akoko (AAU) (n = 402; 199 male and 203 female; overall mean age 23) were studied. The result indicated that 60% of the students (58% male and 62% female) consumed the recommended minimum number of servings of cereal, 50% of the males and 35% of the females in the carbohydrate category while 35% of the males and 42% of the fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
8
29
0
Order By: Relevance
“…Gender differences for the achieved dietary recommendations underline the importance of targeting strategies to improve dietary habits while taking gender into consideration. Our findings also agree with similar gender specific dietary trends observed among Nigerian university students, where more females (42%) than males (35%) achieved the recommendations for meat consumption, consumed adequate quantities of fruits and vegetables (females 40%, males 20%), and consumed milk and milk substitutes (females 25%, males 10%) (32). In agreement, in Greece, female students had higher scores for healthy eating (35).…”
Section: Discussionsupporting
confidence: 90%
“…Gender differences for the achieved dietary recommendations underline the importance of targeting strategies to improve dietary habits while taking gender into consideration. Our findings also agree with similar gender specific dietary trends observed among Nigerian university students, where more females (42%) than males (35%) achieved the recommendations for meat consumption, consumed adequate quantities of fruits and vegetables (females 40%, males 20%), and consumed milk and milk substitutes (females 25%, males 10%) (32). In agreement, in Greece, female students had higher scores for healthy eating (35).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding consumption of dairy foods; encouragement of a sufficient milk intake would be a superior therapeutic approach [65].While the current study reported that, the majority of students were not regularly eat or drink dairy foods. This result may be related to lack of student knowledge about the importance of regular diary food intake.…”
Section: The Association Between Eating Habits and Body Mass Index Ammentioning
confidence: 56%
“…Also, the consumption of raw vegetables and fruits alongside main meals is not a common practice in the student population. This unhealthy picture is typical of a university student population as demonstrated in previous studies which identified poor dietary behavior among university student samples in Jordan [32] and Nigeria [39]. In addition, a report by Al-Rethaiaa et al [40] revealed that most of the students had two meals a day, with frequent consumption of fried foods and snacks, and less frequent consumption of fruits and vegetables.…”
Section: Discussionmentioning
confidence: 73%